Bribe and Bribery Labeling in Kenyan Anti-Corruption Discourse: A Conceptual Metaphor Perspective - Onchoke, Aunga Solomon; Eric, Okwako (Universitas Negeri Semarang, 2020)
Corruption in Kenya has been a particularly large problem since its independence from British rule in 1963. This paper explores the motivation behind a cultural specific metaphor of bribe and bribery labeling in Kenya as seen from the conceptual metaphor viewpoint. The study identifies and explains the different terms relating to a bribe and bribery, describes social-cultural values in Kenya, and accounts for the cognitive processes involved in their interpretation. The data includes a list of terms collected from traffic police officers, public transport workers and commuters from different parts of Kenya. These metaphors were identified by the Metaphor Identification Procedure (MIP) created by Pragglejaz Group (2007) and analyzed using the Cognitive Metaphor Theory from Lakoff and Johnson (1987). The results reveal that language spoken by a society is an essential part of its culture, and the lexical distinctions drawn by each language reflect culturally important features of objects, foods, institutions, games, air we breathe and other activities in the society in which the language operates. We argue that conceptual metaphors are conduits of communication, and it is prudent to apply the cognitive linguistic approach for their better contextual appreciation. This paper concludes by suggesting further avenues for research into socio-cultural metaphors, and by calling for the government to innovate new ways of fighting corruption because the players have invented ingenious ways of communicating about it metaphorically beyond comprehension for a lay person.